2008
DOI: 10.1177/021849230801600303
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspidized Pulmonary Homograft for Truncus Arteriosus Repair

Abstract: Primary repair is preferable to palliation in infants with truncus arteriosus. At our institute, an appropriately small homograft valved conduit is not available for every patient; a bicuspidized pulmonary valve homograft is an alternative. Between December 1996 and August 2005, 24 patients aged 28 days to 21 months with truncus arteriosus underwent primary repair with a homograft valved conduit; bicuspidized homografts were used in 15 of them. In the 18 (75%) patients who survived to hospital discharge, 5-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This is broadly in agreement with other studies, which have demonstrated similar early mortality rates, with the majority of deaths occurring in the early postoperative period. 14,16,19 The actuarial survival in our study was 83.1% AE 6.6% at 30 years, indicating that the majority of patients with CAT survive long term. Similar but less efficacious results have been reported in the literature, with one study demonstrating an 83% actuarial survival at 15 years postoperatively.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This is broadly in agreement with other studies, which have demonstrated similar early mortality rates, with the majority of deaths occurring in the early postoperative period. 14,16,19 The actuarial survival in our study was 83.1% AE 6.6% at 30 years, indicating that the majority of patients with CAT survive long term. Similar but less efficacious results have been reported in the literature, with one study demonstrating an 83% actuarial survival at 15 years postoperatively.…”
Section: Discussionmentioning
confidence: 51%
“…Twenty-four (75%) were neonates. The homograft used in the right ventricular outflow tract was aortic in 24 patients and pulmonary in 8 patients (mean diameter, 15.8 AE 3.5 mm; median diameter, 16 mm [range,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)). The median follow-up was 24.5 years (range, 5.6 months to 43.5 years).Results: There were 3 hospital deaths and 1 late death.…”
mentioning
confidence: 99%
“…Given the shortage of small-sized conduits for these reconstructions in young infants, more readily available larger-sized grafts can be used after size reduction by bicuspidalization [2,3]. The long-term functionality of bicuspidalized grafts in the RV outflow tract (RVOT) has been described by few groups [4][5][6][7]. The results in children with Ross or extended Ross (Konno) procedures have only been reported anecdotally [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…3 , 4 However, some studies have reported limited availability and poor durability of the allografts. 5 , 6 Moreover, the supply of small-sized homografts is also limited. 5 The Contegra conduit, a commercial integrated valved conduit derived from heterogenous bovine jugular vein, was developed as an alternative option.…”
Section: Introductionmentioning
confidence: 99%
“…5 , 6 Moreover, the supply of small-sized homografts is also limited. 5 The Contegra conduit, a commercial integrated valved conduit derived from heterogenous bovine jugular vein, was developed as an alternative option. 7 Early and midterm results of RVOT reconstruction with homografts were good, but only a few studies have reported late outcomes, and there are no available reports from Thailand.…”
Section: Introductionmentioning
confidence: 99%